NiCo-MOF / MXene-CNF aerogel composite material as well as preparation method and application thereof
By growing NiCo-MOF in situ on the surface of MXene-CNF aerogel to form a three-dimensional porous network structure, the problems of MXene material re-stacking and insufficient stability of MOF materials are solved. Significantly improves electrochemical performance and energy storage capacity.
Patent Information
- Application Number
- CN202411228318.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
AI Technical Summary
The sheet structure of MXene material is easy to re-stack, resulting in a decrease in specific surface area and reduced electrochemical performance. The lack of conductivity and stability of MOF materials limits its application in the field of electrochemistry.
The MXene dispersion liquid was prepared by etching MAX phase powder with LiF and hydrochloric acid, and mixed with nanocellulose to freeze it into ice to form MXene-CNF aerogel, and then NiCo-MOF was grown in situ on its surface to form a three-dimensional porous network structure NiCo -MOF/MXene-CNF aerogel composite material.
It effectively avoids irreversible agglomeration and self-stacking of MXene, provides efficient electrolyte ion channels, improves specific surface area and charge storage ability, and enhances electrochemical performance.
Smart Images

Figure CN119132840A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitor electrode materials, and specifically relates to a NiCo-MOF / MXene-CNF aerogel composite material and a preparation method and application thereof. Background Art
[0002] In recent years, supercapacitors have attracted extensive attention due to their many advantages, including fast charge and discharge kinetics, long cycle life, and high power density. MXene is a two-dimensional material composed of transition metal carbides or carbonitrides. It has excellent energy storage performance and is often used as an electrode material for supercapacitors. However, the MXene layer structure is prone to restacking, which reduces the specific surface area of the material, affects the diffusion of ions between layers, and thus reduces the electrochemical performance.
[0003] MOF (metal organic framework material) is a new type of porous crystalline material, also known as porous coordination polymer, which is a type of porous crystalline material formed by metal ions or metal clusters and organic ligand bridges. Metal organic framework materials have special structures such as adjustable pore structure, large specific surface area, high porosity, ordered porous structure and exposed active sites. By changing metal ions and organic functional groups, many metal organic framework materials with unique physical and chemical properties can be synthesized. These characteristics have aroused great interest among scientific researchers, but most MOF materials have poor conductivity and stability, which limits their further application in the field of electrochemistry.
[0004] Therefore, designing and synthesizing MOF and MXene composite materials with specific functional properties can greatly promote the application of MOF and MXene in electrochemistry. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a NiCo-MOF / MXene-CNF aerogel composite material, which can at least solve some of the defects existing in the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] A method for preparing a NiCo-MOF / MXene-CNF aerogel composite material comprises the following steps:
[0008] S1, using LiF and hydrochloric acid to etch the MAX phase powder, washing, ultrasonication, and centrifugation to purify the reaction product to obtain a MXene dispersion;
[0009] S2, mixing the MXene dispersion and nanocellulose evenly, freezing them into ice, and drying them in a freeze drying oven to obtain MXene-CNF aerogel;
[0010] S3, N,N-dimethylformamide, deionized water and alcohol are uniformly mixed, and NiCl2·6H2O, CoCl2·6H2O, trimesic acid and polyvinyl pyrrolidone are added thereto to dissolve to obtain a mixed solution;
[0011] S4. After ultrasonically dispersing the mixed solution, add MXene-CNF aerogel, place it in an oven at 120-200°C for reaction for 6-14 hours, and obtain a NiCo-MOF / MXene-CNF aerogel composite material.
[0012] Furthermore, in step S1, the concentration of hydrochloric acid is 8-10 mol / L, the ratio of the mass of LiF to the volume of hydrochloric acid is 1-3 g:15-30 ml; the MAX phase powder is one of Ti3AlC2, Ti2AlC, and Ti3AlCN, and the mass ratio of the MAX phase powder to LiF is 1:1-3.
[0013] Furthermore, in step S1, the reaction product is first washed with hydrochloric acid and then with deionized water until the solution pH reaches 6-7, and then deionized water is added, and ultrasonic stripping is performed at 0-10°C for 1-2 hours. After the ultrasonic stripping is completed, centrifugation is performed using a centrifugal force of 12000-15000g for 0.5-1.5 hours.
[0014] Furthermore, in step S2, the mass of the nanocellulose is 1 to 10% of the total mass of the MXene dispersion and the nanocellulose.
[0015] Furthermore, in step S3, the volume ratio of N,N-dimethylformamide, deionized water and alcohol is 1:1:1, and the mass ratio of NiCl2·6H2O, CoCl2·6H2O, trimesic acid and polyvinyl pyrrolidone is 1:0.5-2:0.8-1:8-15.
[0016] Furthermore, in step S4, the temperature of ultrasonic dispersion of the mixed solution is 5 to 15° C. and the time is 20 to 40 minutes.
[0017] Furthermore, in step S4, the reaction product is washed with deionized water and alcohol, and then placed in a drying oven at 60° C. for 12 hours for drying.
[0018] In addition, the present invention also provides a NiCo-MOF / MXene-CNF aerogel composite material, which is prepared by the above-mentioned preparation method.
[0019] Furthermore, the specific surface area of the NiCo-MOF / MXene-CNF aerogel composite material is 45 to 73 m 2 g -1; The capacity retention rate of the NiCo-MOF / MXene-CNF aerogel composite material is greater than 70%.
[0020] The present invention also provides an application of the NiCo-MOF / MXene-CNF aerogel composite material, and uses the NiCo-MOF / MXene-CNF aerogel composite material as a supercapacitor electrode material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention forms a NiCo-MOF / MXene-CNF aerogel composite material with a three-dimensional porous network structure by in-situ growing a NiCo-MOF with a two-dimensional nanosheet structure on the surface of a three-dimensional MXene-CNF aerogel. The NiCo-MOF / MXene-CNF aerogel composite material effectively avoids the irreversible agglomeration and self-stacking of the MXene-CNF material and provides an efficient channel for the migration of electrolyte ions.
[0023] (2) The present invention prepares MXene-CNF aerogel by adding nanocellulose to the MXene dispersion. Compared with conventional MXene aerogel, the MXene-CNF aerogel has a better three-dimensional structure forming effect and a more stable three-dimensional structure.
[0024] (3) Compared with pure MXene-CNF aerogel, the NiCo-MOF / MXene-CNF aerogel composite material of the present invention has a larger mass specific capacitance and a better ability to store charge.
[0025] The present invention will be further described in detail below with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a scanning electron microscope image and a high-magnification scanning electron microscope image of the NiCo-MOF / MXene-CNF aerogel composite material prepared in Example 1 of the present invention;
[0027] Figure 2 is the nitrogen adsorption-desorption isotherm of the NiCo-MOF / MXene-CNF aerogel composite material and pure MXene-CNF aerogel prepared in Example 4 of the present invention;
[0028] Figure 3 The NiCo-MOF / MXene-CNF aerogel composite material prepared in Example 4 of the present invention and the pure MXene-CNF aerogel at a scanning rate of 5 mV·s -1 The CV curve comparison chart below;
[0029] Figure 4 The NiCo-MOF / MXene-CNF aerogel composite material prepared in Example 4 of the present invention and the pure MXene-CNF aerogel at a current density of 1A·g -1 The GCD curve comparison chart below;
[0030] Figure 5 is a comparison diagram of CV curves of different products at different scanning rates in Example 4 of the present invention;
[0031] Figure 6 is the oxidation peak current response I of different products in Example 4 of the present invention p The relationship between the square root of the scanning rate v;
[0032] Figure 7 is a comparison diagram of GCD curves of different products at different current densities in Example 4 of the present invention;
[0033] Figure 8 It is a rate performance diagram of different products at different current densities in Example 4 of the present invention. DETAILED DESCRIPTION
[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Embodiment 1:
[0036] This embodiment provides a NiCo-MOF / MXene-CNF aerogel composite material, and its specific preparation process is as follows:
[0037] S1. Use LiF and hydrochloric acid to etch the MAX phase powder. Add 1.6g LiF powder to 20ml 9mol / L hydrochloric acid. After it is completely dissolved, add 1g Ti3AlC2 powder and vigorously stir the reaction at 50℃ for 24h. Wash the reaction product several times with hydrochloric acid and then repeatedly with deionized water until the pH of the solution reaches 6-7. Add deionized water and ultrasonically peel at 0-10℃ for 1.5h to completely peel off the multiple layers into a single layer. After ultrasonication, centrifuge at 12000-15000g for 1h to obtain a single-layer MXene dispersion.
[0038] S2. The MXene dispersion prepared above is mixed with nanocellulose (CNF) and then frozen into ice at -20°C. After it is completely frozen, it is placed in a freeze drying oven and dried for 48 hours to obtain a MXene-CNF aerogel; wherein the amount of nanocellulose (CNF) added is 8% of the total mass of the MXene dispersion and nanocellulose.
[0039] S3. Evenly mix deionized water, alcohol and N,N-dimethylformamide (DMF) in a volume ratio of 1:1:1, and then add 0.0885 g of NiCl2·6H2O and 0.0885 g of CoCl2·6H2O to the uniform solution. After complete dissolution, add 0.075 g of trimesic acid and 0.8 g of polyvinyl pyrrolidone (PVP) to obtain a mixed solution.
[0040] S4. After the mixed solution is dispersed uniformly by ultrasonication at 10°C for 30 minutes, the MXene-CNF aerogel prepared as above is added, and it is placed in an oven at 150°C for reaction for 10 hours. After the reaction is completed, the reaction product is washed several times with deionized water and alcohol, and placed in a drying oven at 60°C for 12 hours to obtain a NiCo-MOF / MXene-CNF aerogel composite material.
[0041] The NiCo-MOF / MXene-CNF aerogel composite material prepared in this example was subjected to electron microscope scanning, and the results are as follows: Figure 1 As shown by Figure 1 The SEM display of Figure a shows that the NiCo-MOF / MXene-CNF aerogel composite material presents a three-dimensional porous network structure, which can effectively avoid the irreversible aggregation and self-stacking of the electrode and provide an efficient channel for the migration of electrolyte ions. Figure 1 From the high-magnification SEM display of Figure b, it can be seen that the network structure surface of the NiCo-MOF / MXene-CNF aerogel composite is covered with NiCo-MOF nanoparticles, presenting an uneven morphology, indicating that the NiCo-MOF / MXene-CNF aerogel composite is successfully prepared, and the structure of the composite material fully utilizes the synergistic effect of the MXene-CNF and NiCo-MOF component structures, which significantly improves the energy storage properties of the composite material.
[0042] Embodiment 2:
[0043] This embodiment provides a NiCo-MOF / MXene-CNF aerogel composite material, and its specific preparation process is as follows:
[0044] S1. Use LiF and hydrochloric acid to etch the MAX phase powder. Add 1.0g LiF powder to 15ml 10mol / L hydrochloric acid. After it is completely dissolved, add 1.0g Ti2AlC powder and vigorously stir the reaction at 50℃ for 24h. Wash the reaction product several times with hydrochloric acid and then repeatedly with deionized water until the pH of the solution reaches 6-7. Add deionized water and ultrasonically peel at 0-10℃ for 1h to completely peel off the multiple layers into a single layer. After ultrasonication, centrifuge at 12000-15000g for 0.5h to obtain a single-layer MXene dispersion.
[0045] S2. The MXene dispersion prepared above is mixed with nanocellulose (CNF) and then frozen into ice at -20°C. After it is completely frozen, it is placed in a freeze drying oven and dried for 48 hours to obtain a MXene-CNF aerogel; wherein the amount of nanocellulose (CNF) added is 10% of the total mass of the MXene dispersion and nanocellulose.
[0046] S3. Evenly mix deionized water, alcohol and N,N-dimethylformamide (DMF) in a volume ratio of 1:1:1, and then add 0.0885 g of NiCl2·6H2O and 0.0442 g of CoCl2·6H2O to the uniform solution. After complete dissolution, add 0.07 g of trimesic acid and 0.7 g of polyvinyl pyrrolidone (PVP) to obtain a mixed solution.
[0047] S4. After the mixed solution is dispersed uniformly by ultrasonication at 15°C for 20 minutes, the MXene-CNF aerogel prepared as above is added, and it is placed in an oven at 120°C for reaction for 8 hours. After the reaction is completed, the reaction product is washed several times with deionized water and alcohol, and placed in a drying oven at 60°C for 12 hours to obtain a NiCo-MOF / MXene-CNF aerogel composite material.
[0048] Embodiment 3:
[0049] This embodiment provides a NiCo-MOF / MXene-CNF aerogel composite material, and its specific preparation process is as follows:
[0050] S1. Use LiF and hydrochloric acid to etch the MAX phase powder. Add 3g of LiF powder to 30ml of 8mol / L hydrochloric acid. After it is completely dissolved, add 1g of Ti3AlCN powder and vigorously stir the reaction at 50°C for 24h. Wash the reaction product several times with hydrochloric acid and then repeatedly with deionized water until the pH of the solution reaches 6-7. Add deionized water and ultrasonically peel at 0-10°C for 2h to completely peel off the multiple layers into a single layer. After ultrasonication, centrifuge at 12000-15000g for 1.5h to obtain a single-layer MXene dispersion.
[0051] S2. The MXene dispersion prepared above is mixed with nanocellulose (CNF) and then frozen into ice at -20°C. After it is completely frozen, it is placed in a freeze drying oven and dried for 48 hours to obtain a MXene-CNF aerogel; wherein the amount of nanocellulose (CNF) added is 1% of the total mass of the MXene dispersion and nanocellulose.
[0052] S3. Mix deionized water, alcohol and N,N-dimethylformamide (DMF) in a volume ratio of 1:1:1, and then add 0.0885 g of NiCl2·6H2O and 0.177 g of CoCl2·6H2O to the uniform solution. After complete dissolution, add 0.088 g of trimesic acid and 1.33 g of polyvinyl pyrrolidone (PVP) to obtain a mixed solution.
[0053] S4. After the mixed solution is dispersed uniformly by ultrasonication at 5°C for 40 minutes, the MXene-CNF aerogel prepared as above is added, and it is placed in an oven at 200°C for reaction for 10 hours. After the reaction is completed, the reaction product is washed several times with deionized water and alcohol, and placed in a drying oven at 60°C for 12 hours to obtain a NiCo-MOF / MXene-CNF aerogel composite material.
[0054] Embodiment 4:
[0055] This example investigates the effect of reaction time on the performance of NiCo-MOF / MXene-CNF aerogel composites during the in-situ growth of NiCo-MOF in the hydrothermal method. The specific process is basically the same as the preparation process of NiCo-MOF / MXene-CNF aerogel composites in the above Example 1, except that the reaction time in the oven in step S4 in the above Example 1 is set to 6h, 10h, and 14h, respectively, for three groups of experiments to obtain three groups of different products.
[0056] The specific surface area of the pure MXene-CNF aerogel prepared in this example and the NiCo-MOF / MXene-CNF aerogel composites prepared at three different reaction times (i.e., 6 h, 10 h, and 14 h) was measured by the specific surface area detection method (BET), and the nitrogen adsorption and desorption isotherms of different products were tested. Figure 2 As shown. Figure 2 The surface area of pure MXene-CNF aerogel is 32 m 2 g -1 The specific surface area of the NiCo-MOF / MXene-CNF aerogel composite material prepared with a reaction time of 6 h is 45 m 2 g -1The specific surface area of the NiCo-MOF / MXene-CNF aerogel composite material prepared with a reaction time of 10 h is 73 m 2 g -1 The specific surface area of the NiCo-MOF / MXene-CNF aerogel composite material prepared with a reaction time of 14 h is 60 m 2 g -1 ; It can be seen that the growth of NiCo-MOF on the surface of MXene-CNF aerogel greatly increases the specific surface area, which in turn increases the charge storage space. The NiCo-MOF / MXene-CNF aerogel composite material obtained by reacting NiCo-MOF with MXene-CNF for 10 hours has the largest specific surface area.
[0057] The pure MXene-CNF aerogel prepared in this example and the NiCo-MOF / MXene-CNF aerogel composites prepared with three different reaction times (i.e., 6 h, 10 h, and 14 h) were measured at the same scan rate (5 mV·s -1 ) under the CV curve is as follows Figure 3 As shown in the figure, under the voltage window of 0-0.7V, the CV curves of NiCo-MOF / MXene-CNF aerogel composites and pure MXene-CNF aerogel prepared with three different reaction times all show redox peaks, indicating that both NiCo-MOF / MXene-CNF aerogel composites and pure MXene-CNF aerogel can undergo fast and reversible Faraday reactions; and compared with pure MXene-CNF aerogel, NiCo-MOF / MXene-CNF aerogel composites exhibit larger response current and integrated area, indicating that the NiCo-MOF grown on the surface of MXene-CNF aerogel has a positive effect on the contrast capacitance, and NiCo-MOF / MXene-CNF aerogel composites have better charge storage capacity; and it can also be seen from the figure that the NiCo-MOF / MXene-CNF aerogel composite prepared with a reaction time of 10h has the largest response current and integrated area.
[0058] The pure MXene-CNF aerogel prepared in this example and the NiCo-MOF / MXene-CNF aerogel composites prepared with three different reaction times (i.e., 6 h, 10 h, and 14 h) were subjected to the same current density (1 A·g -1 ) is as follows: Figure 4 As shown. Figure 4It can be seen that the GCD curves of NiCo-MOF / MXene-CNF aerogel composites and pure MXene-CNF aerogels both have a charge-discharge platform, indicating the pseudocapacitive characteristics of the samples. Compared with pure MXene-CNF aerogels, NiCo-MOF / MXene-CNF aerogel composites exhibit a longer discharge time. It is calculated that the mass specific capacitance of pure MXene-CNF aerogel is 445Fg -1 The mass specific capacitance of NiCo-MOF / MXene-CNF aerogel prepared after 10 h of reaction is 640.9 Fg -1 The mass specific capacitance of NiCo-MOF / MXene-CNF aerogel prepared after 6 h of reaction was 557.8 Fg -1 The mass specific capacitance of NiCo-MOF / MXene-CNF aerogel prepared after 14 h of reaction was 564.9 Fg -1 It can also be seen that different reaction times will affect the electrochemical performance of NiCo-MOF / MXene-CNF aerogel composites. If the reaction time is too short or too long, the mass specific capacitance of NiCo-MOF / MXene-CNF aerogel composites will be low. The mass specific capacitance of NiCo-MOF / MXene-CNF aerogel composites prepared with a reaction time of 10h is the highest, and its ability to store electrical energy is the greatest, which is consistent with the results of the above-mentioned BET method and CV curve measurement.
[0059] The CV curves of the pure MXene-CNF aerogel prepared in this example and the NiCo-MOF / MXene-CNF aerogel composites prepared with three different reaction times (i.e., 6 h, 10 h, and 14 h) at different scanning rates are shown in Figure 2. Figure 5 As shown, Figure a represents pure MXene-CNF aerogel, Figure b represents NiCo-MOF / MXene-CNF aerogel composite material obtained after 6h of reaction, Figure c represents NiCo-MOF / MXene-CNF aerogel composite material obtained after 10h of reaction, and Figure d represents NiCo-MOF / MXene-CNF aerogel composite material obtained after 14h of reaction. Figure 5 It can be seen that all product graphs show redox reaction characteristics. With the increase of scanning rate, the shape of redox peak remains basically unchanged, showing the high reversibility and rate performance of the product. Moreover, with the increase of scanning rate, the electrode polarizes, the oxidation peak moves toward the high voltage direction, and the reduction peak moves toward the low voltage direction.
[0060] Furthermore, in order to explore the charge storage mechanism of the electrode, the above Figure 5 The oxidation peak current response (I p) and the scan rate (v) were studied, and the oxidation peak current response (I p ) and the scanning rate (v) are as follows Figure 6 As shown. Figure 6 It can be seen that I p and the square root of v(v 1 / 2 ) is linearly related, indicating that there is a diffusion-controlled process in the redox reaction; and from Figure 6 It can also be seen that the straight line slope of the NiCo-MOF / MXene-CNF aerogel composite material prepared with a reaction time of 10 h is the largest, which is about 2.5 times that of the pure aerogel electrode, indicating that the NiCo-MOF / MXene-CNF aerogel composite material prepared with a reaction time of 10 h has a faster ion diffusion rate.
[0061] The GCD curves of the pure MXene-CNF aerogel prepared in this example and the NiCo-MOF / MXene-CNF aerogel composites prepared with three different reaction times (i.e., 6 h, 10 h, and 14 h) at different current densities are shown in Figure 2. Figure 7 As shown, Figure a represents pure MXene-CNF aerogel, Figure b represents NiCo-MOF / MXene-CNF aerogel composite material obtained after 6h of reaction, Figure c represents NiCo-MOF / MXene-CNF aerogel composite material obtained after 10h of reaction, and Figure d represents NiCo-MOF / MXene-CNF aerogel composite material obtained after 14h of reaction. Figure 7 It can be seen that with the increase of current density, the charge and discharge time of all products gradually shortens, and the charging time and discharging time of all product curves are basically the same, indicating that the products prepared in this embodiment have higher coulombic efficiency at different current densities.
[0062] The rate performance of the pure MXene-CNF aerogel prepared in this example and the NiCo-MOF / MXene-CNF aerogel composites prepared with three different reaction times (i.e., 6 h, 10 h, and 14 h) at different current densities is shown in Figure 2. Figure 8 As shown. Figure 8 It can be seen that at a current density of 1A·g -1 Under these conditions, the specific capacities of pure MXene-CNF aerogel and NiCo-MOF / MXene-CNF aerogel composites prepared with reaction time of 6h, 10h, and 14h were 429mA h g -1 、510mA hg -1 、590mA hg -1 、500mAhg -1 , at a current density of 15A·g -1Under these conditions, the specific capacities of pure MXene-CNF aerogel and NiCo-MOF / MXene-CNF aerogel composites prepared with reaction time of 6h, 10h, and 14h were 294mA h g -1 、360mA hg -1 、450mA hg -1 and 351mA hg -1 ; From this, it can be calculated that the capacity retention rates of pure MXene-CNF aerogel and NiCo-MOF / MXene-CNF aerogel composites prepared with reaction times of 6h, 10h, and 14h are 68.53%, 70.59%, 76.27%, and 70.21%, respectively.
[0063] The above examples are merely illustrative of the present invention and do not constitute a limitation on the protection scope of the present invention. All designs that are the same or similar to the present invention fall within the protection scope of the present invention.
Claims
1. A method for preparing a NiCo-MOF / MXene-CNF aerogel composite material, characterized in that: The steps include: S1, using LiF and hydrochloric acid to etch the MAX phase powder, washing, ultrasonication, and centrifugation to purify the reaction product to obtain a MXene dispersion; S2, mixing the MXene dispersion and nanocellulose evenly, freezing them into ice, and drying them in a freeze drying oven to obtain MXene-CNF aerogel; S3, N,N-dimethylformamide, deionized water and alcohol are uniformly mixed, and NiCl2·6H2O, CoCl2·6H2O, trimesic acid and polyvinyl pyrrolidone are added thereto to dissolve to obtain a mixed solution; S4. After ultrasonically dispersing the mixed solution, add MXene-CNF aerogel, place it in an oven at 120-200°C to react for 6-14 hours, and obtain a NiCo-MOF / MXene-CNF aerogel composite material.
2. The method for preparing the NiCo-MOF / MXene-CNF aerogel composite material according to claim 1, characterized in that: In the step S1, the concentration of hydrochloric acid is 8-10 mol / L, and the ratio of the mass of LiF to the volume of hydrochloric acid is 1-3 g:15-30 ml; the MAX phase powder is one of Ti3AlC2, Ti2AlC, and Ti3AlCN, and the mass ratio of the MAX phase powder to LiF is 1:1-3.
3. The method for preparing the NiCo-MOF / MXene-CNF aerogel composite material according to claim 1, characterized in that: In the step S1, the reaction product is first washed with hydrochloric acid and then with deionized water until the solution pH reaches 6-7, and then deionized water is added, and ultrasonic stripping is performed at 0-10° C. for 1-2 hours. After the ultrasonic stripping is completed, centrifugation is performed at a centrifugal force of 12000-15000 g for 0.5-1.5 hours.
4. The method for preparing the NiCo-MOF / MXene-CNF aerogel composite material according to claim 1, characterized in that: In the step S2, the mass of the nanocellulose is 1 to 10% of the total mass of the MXene dispersion and the nanocellulose.
5. The method for preparing the NiCo-MOF / MXene-CNF aerogel composite material according to claim 1, characterized in that: In step S3, the volume ratio of N,N-dimethylformamide, deionized water and alcohol is 1:1:1, and the mass ratio of NiCl2·6H2O, CoCl2·6H2O, trimesic acid and polyvinyl pyrrolidone is 1:0.5-2:0.8-1:8-15.
6. The method for preparing the NiCo-MOF / MXene-CNF aerogel composite material according to claim 1, characterized in that: In the step S4, the temperature of ultrasonic dispersion of the mixed solution is 5 to 15° C. and the time is 20 to 40 minutes.
7. The method for preparing the NiCo-MOF / MXene-CNF aerogel composite material according to claim 1, characterized in that: In step S4, the reaction product is washed with deionized water and alcohol, and then placed in a drying oven at 60° C. for 12 hours for drying.
8. A NiCo-MOF / MXene-CNF aerogel composite material, characterized in that: The preparation method is described in any one of claims 1 to 7.
9. The NiCo-MOF / MXene-CNF aerogel composite material according to claim 8, characterized in that The specific surface area of the NiCo-MOF / MXene-CNF aerogel composite material is 45 to 73 m 2 g -1 ; The capacity retention rate of the NiCo-MOF / MXene-CNF aerogel composite material is greater than 70%.
10. Use of the NiCo-MOF / MXene-CNF aerogel composite material according to claim 8 or 9, characterized in that: NiCo-MOF / MXene-CNF aerogel composites are used as supercapacitor electrode materials.
Citation Information
Cited By
SAs-MXene / MOF-graphite aerogel composite material, negative electrode plate and preparation method
CN120854555A
